2011
DOI: 10.1111/j.1574-695x.2011.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor-2-activating bifidobacteria strains differentially regulate inflammatory cytokines in the porcine intestinal epithelial cell culture system: finding new anti-inflammatory immunobiotics

Abstract: A total of 23 strains of bifidobacteria taxonomically belonging to five species were tested for their potent immunomodulatory effect using a combination of two methods: the NF-κB-reporter assay using a toll-like receptor 2-expressing transfectant (HEK(pTLR2) system) and the mitogenic assay using porcine Peyer's patches immunocompetent cells. Among the four preselected strains from different immunomodulatory groups, Bifidobacterium breve MCC-117 was able to efficiently modulate the inflammatory response trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 33 publications
6
59
0
Order By: Relevance
“…A recent study in Caco-2 cells demonstrated that L. rhamnosus GG is able to counteract ETEC-induced upregulation of IL-1␤ and TNF-␣ and the downregulation of TGF-␤1 expression, and consequently it prevents cytokine deregulation (31). In addition, comparative studies between L. rhamnosus GG and Bifidobacterium animalis MB5 (31) and between different bifidobacterial strains (8) demonstrated that the effects of individual probiotic strains on the inflammatory responses in IECs differ (8,31). These findings indicate that some probiotic LAB strains may be beneficial for preventing inflammatory response-mediated damage during weaning.…”
Section: Discussionmentioning
confidence: 83%
“…A recent study in Caco-2 cells demonstrated that L. rhamnosus GG is able to counteract ETEC-induced upregulation of IL-1␤ and TNF-␣ and the downregulation of TGF-␤1 expression, and consequently it prevents cytokine deregulation (31). In addition, comparative studies between L. rhamnosus GG and Bifidobacterium animalis MB5 (31) and between different bifidobacterial strains (8) demonstrated that the effects of individual probiotic strains on the inflammatory responses in IECs differ (8,31). These findings indicate that some probiotic LAB strains may be beneficial for preventing inflammatory response-mediated damage during weaning.…”
Section: Discussionmentioning
confidence: 83%
“…Next, harvested PP or MLN cells were subjected to hypertonic rescue in an equal volume of 1.5% NaCl. Finally, immune cells were fractionated using Lympholyte-mammal (Cedarlane, Hornby, Ontario, Canada) density gradient centrifugation, and the isolated immune cells were suspended in complete RPMI 1640 (Sigma, St. Louis, MO, USA) supplemented with 10% FCS (Sigma), 50 g/mL and 50 g/mL penicillin-streptomycin (Gibco ® , Life Tech., Carlsbad, CA, USA) (Fujie et al, 2011).…”
Section: Isolation Of Immunocompetent Cells From Swine Peyer Patches mentioning
confidence: 99%
“…The mitogenicity assay was performed as described previously (Fujie et al, 2011). Briefly, PPs or MLN immunocompetent cells (2 × 10 5 cells/well) were placed in a round ninety-six-well microplate (SUMILON ® , Sumitomo Bakelite Co. Ltd., Tokyo, Japan) and incubated at 5% CO 2 , 37 • C for 48 h in complete RPMI 1640 medium (Sigma, St. Louis, MO, USA) supplemented with 2% FCS.…”
Section: Mitogenicity Assaymentioning
confidence: 99%
“…Two-step real-time quantitative PCR (qPCR) was used to characterize the expression of specific mRNAs in immune cells (13,28). Total RNA was isolated from individual samples of porcine APCs using TRIzol reagent.…”
Section: Isolation Of Cd172amentioning
confidence: 99%